2015
DOI: 10.1144/sp414.12
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic susceptibility application: a window onto ancient environments and climatic variations: foreword

Abstract: Magnetic susceptibility (MS) is a powerful tool, which is being applied increasingly on sedimentary rocks to constrain stratigraphic correlations, or as a palaeo-environmental or palaeoclimatic tool. The origin of the magnetic minerals responsible for the variations in MS can be linked to various phenomena such as detrital inputs, pedogenesis, bacterial precipitation or diagenesis. Therefore, it is critical to improve our knowledge of the origin of the MS signal in order to apply it for correlations or as a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…However, the oxygen in the structure of the helminth eggs ( 58 , 59 ) also has attribution in the magnitude of a magnetic field, due to its high magnetic susceptibility ( 60 ). Therefore, the magnetic field originated from this component ( 60 , 61 ) as well as water layers ( 61 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the oxygen in the structure of the helminth eggs ( 58 , 59 ) also has attribution in the magnitude of a magnetic field, due to its high magnetic susceptibility ( 60 ). Therefore, the magnetic field originated from this component ( 60 , 61 ) as well as water layers ( 61 ).…”
Section: Resultsmentioning
confidence: 99%
“…Their results suggested the high potential of χ signal for global correlation in ancient sedimentary sequences. Whereas promising, these results lack the geochemical and magnetic basis that are now regarded as crucial prior to any interpretation or use of the χ signal (e.g., Da Silva et al, 2015).…”
Section: Reliability Of χ Records For Long-distance Correlation Of MImentioning
confidence: 90%
“…Despite the remagnetization highlighted in the NE Rhenohercynian Massif and Ardennes (Molina Garza and Zijderveld, 1996;Zwing et al, 2002Zwing et al, , 2005Zegers et al, 2003), Riquier et al (2010) and Da Silva et al (2013) demonstrated that the primary depositionally-induced χ signal was at least partly preserved and that it could be used for paleoenvironmental and paleoclimatic interpretations. Therefore, it is essential to test the origin of the magnetic signal through the combined use of geochemical, facies analyses and hysteresis measurements (Riquier et al, 2010;Da Silva et al, 2015) before applying χ as a paleoclimatic or correlation tool for sections at any scale.…”
Section: Introductionmentioning
confidence: 99%
“…MS (and other magnetic properties as e.g. the isothermal remanent magnetization) often traces terrigenous input vs. authigenic bioproduction, and MS is a frequently applied and valuable proxy (e.g., Da Silva et al, 2015 and references therein; Table 1). In marine environments, MS generally traces the influx of terrestrial material, and high MS relates to high fluvial or dust influx.…”
Section: Magnetic Susceptibility Loggingmentioning
confidence: 99%